Diurnal Timing Dependent Alterations in Gut Microbial Composition Are Synchronously Linked to Salt-Sensitive Hypertension and Renal Damage. Issue 1 (July 2020) - Chakraborty, Saroj; Mandal, Juthika; Cheng, Xi; Galla, Sarah; Hindupur, Anay; Saha, Piu; Yeoh, Beng San; Mell, Blair; Yeo, Ji-Youn; Vijay-Kumar, Matam; Yang, Tao; Joe, Bina
Abstract : Alterations of diurnal rhythms of blood pressure (BP) and reshaping of gut microbiota are both independently associated with hypertension. However, the relationships between biorhythms of BP and gut microbial composition are unknown. We hypothesized that diurnal timing-associated alterations of microbial compositions are synchronous with diurnal rhythmicity, dip in BP, and renal function. To test this hypothesis, Dahl salt-sensitive (S) rats on low- and high-salt diets were examined for time of day effects on gut microbiota, BP, and indicators of renal damage. Major shifts in night and day patterns of specific groups of microbiota were observed between the dark (active) and light (rest) phases, which correlated with diurnal rhythmicity of BP. The diurnal abundance of Firmicutes, Bacteroidetes, and Actinobacteria were independently associated with BP. Discrete bacterial taxa were observed to correlate independently or interactively with one or more of the following 3 factors: (1) BP rhythm, (2) dietary salt, and (3) dip in BP. Phylogenetic Investigation of Communities revealed diurnal timing effects on microbial pathways, characterized by upregulated biosynthetic processes during the active phase of host, and upregulated degradation pathways of metabolites in the resting phase. Additional metagenomics functional pathways with rhythm variations were noted for aromatic amino acid metabolism and taurine metabolism. These diurnal timing dependent changes in microbiota, their functional pathways, and BP dip were associated with concerted effects of the levels of renal lipocalin 2 and kidney injury molecule-1 expression. These data provide evidence for a firm and concerted diurnal timing effects of BP, renal damage, and select microbial communities. Abstract : Supplemental Digital Content is available in the text.